Direct use of design criteria in genetic algorithm-based controller optimization. - Kim, Yoon-Jun
In this study, genetic algorithms are applied to design controllers for the wind excited vibration reduction of a 76 story tall building in the second generation benchmark problem. Design criteria and constraints including the comfort requirement for building occupants and the control robustness are directly incorporated in the formulation and evaluation of the fitness and penalty function of the genetic algorithm based control design. The method is efficient in obtaining optimal design with multiple constraint conditions. Two controllers are designed with realistic constraints and different robustness criteria. The corresponding results are investigated and compared with LQG optimal control results.
Keywords: Structural control; Genetic algorithms; Wind; Dynamics; Building; Embedding